Analisis Strategi Pemasaran Komoditas Pala (Myristica fragrans) Di Kecamatan Bacan Timur Selatan - Nurmaya Bakir; Hamidin Rasulu; Suryati Tjokrodiningrat; Suratman Sudjud; Sri Soenarsih; Yusri Sapsuha (Jurnal Pertanian Khairun, 2025)
Nutmeg is one of the leading plantation commodities in South Bacan Timur Subdistrict, South Halmahera Regency. However, its productivity and product quality have not yet reached optimal levels compared to other production centers. In addition, the lack of an integrated marketing system and the dominance of intermediary traders have resulted in a relatively weak bargaining position for farmers. This study aims to identify the internal and external factors affecting nutmeg marketing and to determine the most priority marketing and development strategies for the nutmeg commodity. The research was conducted from August to November 2025 in Tabajaya, Wayaua, and Tabangame villages, involving 30 nutmeg farmers and 5 traders. The analytical methods used were SWOT analysis to formulate alternative strategies and the Analytic Hierarchy Process (AHP) to determine strategy priorities. The results of the SWOT analysis identified four marketing strategies for farmers, namely Participatory Marketing Based on Efficiency, Quality Standardization as a Partnership Requirement, Farmers’ Financial Independence, and Community-Based Quality Control. Meanwhile, four marketing strategies for traders were identified: Volume and Logistics Expansion, Cash Flow Acceleration and Fixed Contracts, Purchase Price Leadership, and Risk Management with a “Just-in-Time” approach. The AHP results indicate that the priority strategy for farmers is quality standardization as a partnership requirement with a weight of 0.3780, while for traders it is volume and logistics expansion with a weight of 0.4106. These strategies are expected to improve marketing efficiency and welfare.